Pengaruh penambahan daun widuri pada pakan basal rumput kumeterhadap pertambahan berat badan kambing jantan lokal - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This study was undertaken to study the effects of Widuri leaves (Callotropis giganteae) supplements on the daily weightgain of male local goat by using Kume grass (sorghesm plumosum var. Timorens) as a basal diet. Four groups of four local goat (8-18 month of age) with an average body weight of 15.28 kg were fed the following diets : Kume grass + 26.73% of Widuri leaves (RW1)